2014
DOI: 10.1016/j.chembiol.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling Reveals PAFAH1B3 as a Critical Driver of Breast Cancer Pathogenicity

Abstract: Many studies have identified metabolic pathways that underlie cellular transformation, but the metabolic drivers of cancer progression remain less well understood. The Hippo transducer pathway has been shown to confer malignant traits on breast cancer cells. In this study, we used metabolic mapping platforms to identify biochemical drivers of cellular transformation and malignant progression driven through RAS and the Hippo pathway in breast cancer, and identified platelet activating factor acetylhydrolase 1B3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 37 publications
9
82
0
Order By: Relevance
“…We have previously reported MG-mediated carbonyl stress, assessed by argpyrimidine adducts detection, in a series of breast cancer lesions (Chiavarina et al, 2014). Recent reports highlighted the importance of glucose metabolism for the regulation of YAP activity in cancer cells (DeRan et al, 2014; Enzo et al., 2015; Mulvihill et al, 2014). To explore possible links between YAP activity and carbonyl stress, we performed immunohistochemistry staining of YAP on a series of 87 breast tumors categorized as high and low-to-intermediate carbonyl stress tumors based on their endogenous argpyrimidine level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported MG-mediated carbonyl stress, assessed by argpyrimidine adducts detection, in a series of breast cancer lesions (Chiavarina et al, 2014). Recent reports highlighted the importance of glucose metabolism for the regulation of YAP activity in cancer cells (DeRan et al, 2014; Enzo et al., 2015; Mulvihill et al, 2014). To explore possible links between YAP activity and carbonyl stress, we performed immunohistochemistry staining of YAP on a series of 87 breast tumors categorized as high and low-to-intermediate carbonyl stress tumors based on their endogenous argpyrimidine level.…”
Section: Resultsmentioning
confidence: 99%
“…Enzo and collaborators (Enzo et al., 2015) have recently demonstrated that aerobic glycolysis impacts on YAP/TAZ transcriptional activity through a mechanism involving phosphofructokinase 1 binding to TEAD transcription factors. A recent metabolic profiling study using breast cancer progression cellular models reported the induction of several glycolytic enzymes upon constitutive activation of YAP/TAZ factors (Mulvihill et al, 2014). Therefore, it is tempting to speculate that MG could regulate key glycolytic enzymes expression in a YAP-dependent manner thus creating a mutual regulatory loop where glycolysis-induced MG stress favors YAP activity, which in turn activates glycolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomic analyses were conducted using previously described methods (Benjamin et al, 2013, 2014,2015; Long et al, 2011; Mulvihill et al, 2014). More details can be found in Supplemental Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Mulvihill et al conducted proteomic profiling and identified dysregulated metabolic pathways in a model of breast cancer progression and then used RNA interference-mediated knockdown to screen for dysregulated enzymes [34]. Knockdown of the expression of the α 1 and α 2 catalytic subunits of PAF-AH I markedly impairs proliferation, survival, and migration of breast cancer cells.…”
Section: Cancer Pathogenicitymentioning
confidence: 99%